Fisheries off the United States coasts : agreement between the United States of America and Iceland, amending and extending the agreement of September 21, 1984, as amended and extended, effected by exchange of notes, signed at Washington February 11 and April 5, 1991. - Iceland.; United States. 1984 Sept. 21. Protocols, etc., 1991 Feb. 11. Treaties, etc. Iceland.; United States. Department of State. (Washington, D.C. : Dept. of State : For sale by the Supt. of Docs., U.S. G.P.O., 1993)
Mode of access: Internet.